Exploring the relationship between integrated marketing communications and decentralised organisational structure: a heuristics perspective. Issue 2 (21st February 2022) - Ozuem, Wilson; Howell, Kerry; Lancaster, Geoff
Abstract : Purpose: The concept of integrated marketing communications (IMC) was developed in the 1990s and has gained significant interest from academics and practitioners, yet it is seldom achieved in practice. The purpose of this paper is to investigate the reasons behind this assertion. Design/methodology/approach: Knowledge needed for this study was generated from a case study of a global company, operating a decentralized organizational structure in the health-care industry. Findings: Thirty semi-structured interviews were performed with marketing employees and management. This paper contributes to facilitating marketing communications by developing a conceptual model using strategic guiding principles to align marketing communication activities. Research limitations/implications: Thematic analysis generated three integration areas: efficiency, consistency and relationship. Practical implications: The information generated from this research paper should assist managers when attempting to implement an integrated approach to marketing communications. Social implications: As IMC is intertwined with the concept of strategy, if it is implemented as a strategic process; similar social influences are relevant for strategic IMC implementation. Originality/value: This paper contributes to facilitating marketing communications by developing a conceptual model using strategic guiding principles to align marketing communication activities.